Pertemuan Agama dan Ilmu Pengetahuan dalam Dinamika Masyarakat Kontemporer - Marsintha Dameria; Ricky Sutjiadi (LPPM STT Baptis Kalvari, 2023)
In the dynamics of contemporary society, the encounter between religion and science has become a relevant and significant subject. Technological developments, particularly through the use of social media, have broadened and deepened relationships between individuals, creating new complexities in social interactions. This phenomenon encourages the need for a broader and deeper understanding of the relationship between religion and science. This research aims to investigate the interactions, challenges, conflicts, and potential for collaboration between these two fields in the context of an ever-changing modern society. Through an interdisciplinary approach, this research tries to identify the factors that influence changes in understanding of religion, as well as how science contributes to these dynamics. This writing explores how religion and science meet in the context of modern society, outlining the challenges, conflicts, and potential for collaboration between the two. It will also look at the impact of these dynamics on understanding religion, science and humanity more broadly. This research will analyze the role of contemporary society in shaping the relationship between religion and science, and how it impacts individual values, ethics and identity. The main aim of this research is to provide in-depth insight into the role of religion and science in modern society and the way these dynamics continue to evolve as times change. It is hoped that the results of this research can provide deeper insight into the complex relationship between religion and science in contemporary society, as well as its implications for social and cultural changes that continue to develop.